The impact of cultural tourism experience on cultural identity: A case study of Mazu culture - Mian Wang; Hee Seung Lee; Wen Qiang Chen (PLoS ONE, 2026)
Cultural heritage tourism is pivotal for fostering cultural identity, yet the psychological pathway from experience to identity formation in non-Western, folk-religious contexts remains unclear. This study examines this process within Mazu culture (a UNESCO intangible heritage), proposing a serial mediation model where 4E experiences (i.e., Entertainment, Educational, Escapist, Esthetic) foster emotional resonance, which in turn strengthens cultural identity, ultimately leading to place identity. Data from 583 tourists at Meizhou Island were analyzed using structural equation modeling and bootstrap tests. The findings reveal that all 4E dimensions significantly enhance emotional resonance, with the Escapist experience being the most potent. Crucially, the sequential mediation of emotional resonance and cultural identity was confirmed for 4E experiences, with the escapist experience exhibiting a complete mediation on place identity. Notably, Educational experience influenced cultural identity only indirectly via emotional resonance. As the first to empirically validate this complete “experience-emotion-identity” chain, this study refines the S-O-R paradigm by delineating its internal psychological sequence and highlights the paramount role of escapist immersion in folk-religious tourism, offering actionable insights for destination management and sustainable heritage preservation.